The Potential Role of SP-G and PLUNC in Tumor Pathogenesis and Wound Healing in the Human Larynx - Aurelius Scheer; Lars Bräuer; Markus Eckstein; Heinrich Iro; Friedrich Paulsen; Fabian Garreis; Martin Schicht; Antoniu-Oreste Gostian (Biomedicines)
Background: Immunological and rheological properties are important factors of the surfactant protein (SP) family, whose impact on tumorigenesis is not yet known, although some SPs have been identified as tumor marker candidates for various malignancies. This study describes the detection of the two surfactant family proteins SP-G and PLUNC in healthy glottis, the presence of SP-G in glottic cancer, and the in vitro tissue regeneration potential of SP-G and PLUNC on epithelial cells. Methods: The expression and distribution of SP-G and PLUNC were investigated immunohistochemically in squamous cell carcinomas of the vocal folds. The expression of both proteins was analyzed by Western blot in micro-dissected healthy vocal fold mucosa from body donors. The hypopharyngeal squamous carcinoma cell line (FaDu) was used as an in vitro model for wound healing experiments with Electric cell–substrate impedance sensing (ECIS). Results: The results show the presence of SP-G and PLUNC in epithelial cells of the healthy vocal folds and the submucosal glands of the vestibular folds. SP-G was detected in squamous cell carcinomas of the vocal folds. SP-G and PLUNC show accelerated wound healing of FaDu cells in vitro. Conclusions: SP-G and PLUNC were first detected in the vocal fold of the human larynx. SP-G shows a distinct presence in glottic carcinoma, whose relevance needs to be determined in future studies. SP-G and PLUNC exhibit a positive influence on the repair mechanisms of epithelial lesions of the glottis. The data presented form the basis for follow-up studies focusing on the impact of SP-G in glottic cancer development and the potentially meaningful clinical effect of SP-G and PLUNC on tissue repair of the human vocal fold.